CHEMICAL COMPOSITION AND PEDOGENESIS OF SOILS OF AGRICULTURAL COLLEGE FARM, NAIRA, ANDHRA PRADESH - P. GURUMURTHY; T. SREELATHA (The Journal of Research ANGRAU, 2023)
The study on elemental composition and pedogenesis of soils of Agricultural College farm, Naira of Srikakulam district was carried-out during 2021. The soils were developed from granite-gneiss parent material. Total silica (SiO2) content of soils ranged from 50.5 to 74.6 percentage. Silica content in general decreased with soil depth, while sesquioxides (R2O3), alumina (Al2O3), iron oxide (Fe2O3), CaO, K2O, Na2O, MnO were found increasing with depth. High silica/ sesquioxide ratio of soils indicated siliceous nature of soils. The aluminum oxide content of the profiles varied from 15.80% to 26.25%. Highest value was reported in lowland profile, whereas, the lowest value was recorded in rainfed upland profile. Iron oxide content varied from 5.04% to 8.50%. Iron oxide content showed slight variation within profiles. Among the other oxides, CaO > MgO > K2O > Na2O was of the order as the soils were developed under semi-arid climate, wherein, basic cations have accumulated in these soil profiles due to limited leaching. The molar concentration of silica (SiO2) ranged from 0.841 to 1.24 moles, and molar concentration of sesquioxide ranged from 0.191 to 0.313 moles. The molar ratio of SiO2 / R2O3 varied from 2.68 to 6.51 in different soil profiles. The SiO2 / Al2O3 ratio varied from 3.33 to 8.02. These wider molar ratios indicated salacious nature of parent material and due to dominance of silica among chemical fractions. Midland (P3) and lowland (P4) soil profiles showed silt/clay ratio of less than 0.45 and upland profiles showed more than 0.45 indicating relatively advanced weathering in mid and lowland profiles while it was moderate weathering in upland profiles. The Weathering Index of Parker (WIP) values of the soils of study area ranged between 2.8 and 32.4. The lower WIP values (2.8 to 8.1) were associated with rainfed uplands and higher values of 14.7- 32.4 with irrigated low lands. The PIA values ranged from 67 to 97 tend to decrease with the depth in all profiles. The profiles examined have the CIA values varied from 66 to 95 indicating high to intense weathering. The CIA values decreased with depth in all the profiles. The surface horizons of P1 and P2 soil profiles were classified as moderately weathered. On the other hand, all subsurface horizons of these two profiles were highly weathered. However, in profiles P3 and P4 the CIA values ranged between 68 to 90 indicating that these soils were highly weathered. CIW values closely followed the trend of CIA values. The bases/R2O3 values of all profiles ranged from 0.061 to 0.608 and found increased with soil depth in all the profiles. Relatively higher values of bases/R2O3 were found in P4 (low lands) indicating base rich character. Middle land and lowland black soil profiles showed silt/clay ratio of less than 0.45 and upland profiles showed morethan 0.45 indicating relatively advanced weathering in mid and lowland profiles while moderate weathering in upland profiles.